Effect of concrete properties and prestressing steel indentation types on the development length and flexural capacity of pretensioned concrete members - Momeni, Amir Farid (Kansas State University, 2016)
A study was conducted to determine the effect of different concrete properties and prestressing steel indentation types on development length and flexural capacity of pretensioned members. Wires and strands commonly used in the manufacturing of prestressed concrete railroad ties worldwide were selected for the study. Thirteen different 5.32-mm-diameter prestressing wire types and six different strands (four, seven-wire strands and two, three-wire strands) were used to cast prisms with a square cross section. The ratio of concrete to prestressed steel in the test prism’s cross section was representable of typical concrete railroad ties. Thus, geometrical and mechanical properties of test prisms were representative of actual ties in the railroad industry. To understand the effect of concrete-release strengths and slumps on development length, all parameters were kept constant in the prisms except concrete-release strength and slump. To manufacture prisms with different release strengths, all four wires/strands were pulled and detensioned gradually when the concrete compressive strength reached 3500 (24.13 MPa), 4500 (31.03 MPa), and 6000 (41.37 MPa) psi. To determine the effect of different slumps on development length, prisms with different slumps of 3 in. (7.6 cm), 6 in. (15.2 cm), and 9 in. (22.9 cm) were manufactured and all other parameters were kept constant in prisms. All prisms were tested in three-point bending at different spans to obtain estimations of development length based on type of reinforcement, concrete-release strength, and concrete slump. Lastly, a design equation was developed based on experimental data for prediction of development length. In the last phase of load tests, cyclic-loading tests were conducted on the prisms manufactured with wires to evaluate the bond performance of wires with different indentation types under cyclic loading. A total of 210 load tests, including 14 cyclic tests, were conducted. The monotonic-load tests revealed a large difference in the development length of pretensioned concrete members manufactured with different wire/strand types and different concrete-release strengths. Also, the cyclic-load tests revealed a significant difference in bond performance of different wire types under cyclic loading compared to monotonic loading.
Keywords: Pretensioned prestressed; Wire indentation; Strand indentation; Concrete release strength; Development length; Railroad ties